A Preparative (structural) and Spectroscopic Study of Activated Carbon Derived from Date Pits by Calcium Chloride Treatment - Rahi, Hussein Ali; Ali, Nathera Abbas (Iraqi Journal of Physics, 2025)
This study explores the preparation, structural, and spectroscopic characterization of activated carbon derived from date pits using calcium chloride as an activating agent. Date pits, an abundant agricultural by-product, were processed into activated carbon through chemical activation with varying ratios of calcium chloride. The resulting activated carbon samples were thoroughly analyzed using X-ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FE-SEM), Fourier-transform Infrared Spectroscopy (FT-IR), and Energy Dispersive X-ray Spectroscopy (EDX). XRD analysis confirmed the presence of crystalline and amorphous carbon phases, with diffraction peaks corresponding to the 101, 110, and 20 planes, indicating successful carbonization and the formation of ordered structures. FE-SEM images showed that pores grew significantly, with pores that were bigger and more noticeable in samples that were activated with higher concentrations of calcium chloride, meaning they had more surface area. FTIR spectra showed increased conjugated C=C double bonds after activation, creating a more porous and chemically active structure. The EDX analysis revealed that the most common elements were carbon and chlorine, suggesting a successful addition of calcium chloride. Other trace elements like phosphorus, sodium, and magnesium were detected, which can be due to the date pits or impurities.